NEW ALGORITHMS FOR SOLVING THE FUZZY CLUSTERING PROBLEM - Kamel, M.S. (2020)
Two new algorithms for fuzzy clustering are presented. Convergence of the proposed algorithms is proved. An empirical study of their convergence behavior is discussed. The performance of the new algorithms is compared with the fuzzy c-means algorithm by testing them on four published data sets. Experimental results show that the new algorithms are faster and lead to computational savings.